AKTIVITAS HARIAN KADAL Mabuya multifasciata DAN KADALTachydromus sexlineatus YANG HIDUP SIMPATRIK DI PERKEBUNAN KAKAO (REPTILIA: LACERTILIA) - Hellen Kurniati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
Dial activity of two sympatric lizard Mabuya multifasciata and Tachydromus sexlineatus in cacao plantation under four weather conditions (sunny, little bit cloudly, cloudly, and sunny with wet surface ground) were observed. M. multifasciata were active as long as the light condition permitted, they were active also even on cloudly and fine wet surface ground when T. sexlineatus were not active. The number of active individual of T. sexlineatus was influenced by the number of active individual of M. multifasciata. This mechanism was seem to avoid competition between two species.